CATEGORY SHIFTS FOUND AT BUKU BAHASA INGGRIS UNTUK PEMANDU WISATA: A TRANSLATION STUDY - Putu Nadia Pramesti (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2023)
This study aims to analyze the category shift from the translation study at tour guide vocabularyin translation by Catford (1965). English is the source language and Indonesian is the targetlanguage. Divided into two major types of shift are identified: ‘Level Shift’ and ‘Category shift. Aqualitative research method was used to collect and analyze data. The data collected in this studywas document riview. The document riview method was implemented by non-participation andemployed note-taking technique to gather relevant data from Buku Bahasa Inggris untuk pemanduwisata. The data analysis used in this study is descriptive linguistic analysis which attempts to explainthe standard forms of language. The results showed that conducted found that there are 25 categoryshift, including 9 structure shift, 2 class shift, 10 unit shift and 4 intra-system shift from the resultsof abstract translations of scientific articles using tour guide vocabulary. As a conclution of 25 totaldata, it was found that the most frequently occurring data was unit shift with a record of 10 timesand the least frequently occurring data was class shift, which was 2 times.